Techno-economic Analysis of Liquid Petroleum Gas Fueled Vehicles as Public Transportation in Indonesia - Setiyo, Muji; Soeparman, Sudjito; Hamidi, Nurkholis; Wahyudi, Slamet (International Journal of Energy Economics and Policy, 2016)
In Indonesia, the use of LPG in vehicles has been promoted through government policy since 1988. However, the progress has not significantly run. Therefore, this paper presents the techno-economic analysis of LPG as road vehicles fuel alternative in comparison with gasoline RON 88 and RON 92 for public transportation in Indonesia. The techno-economic analysis is considered running cost, break-even point (BEP) distance, net present value (NPV), internal rate of return (IRR), payback period, and sensitivity analysis. This analysis indicates that the BEP distance of public transportation vehicles are approximating at 55,351 km compared to gasoline RON 92 and 93,168 km compared to gasoline RON 88. Meanwhile, the result of the investment analysis shows that the investment feasibility indicators which include NPV, IRR, and payback period show the investment was feasible but the investment is sensitive to fuel cost ratio between LPG and gasoline. Keywords: LPG vehicles, running costs, investment feasibility JEL Classifications: M21, O31, Q43